ANALISIS INOVASI PENGEMBANGAN ORGANISASI PADA PEMERINTAH DESA WUKIRSARI KABUPATEN SLEMAN - Hanantyo Sri Nugroho; Agustina Rahmawati (Jurnal Agregasi : Aksi Reformasi Government dalam Demokrasi, 2020)
This study examines the success factors of organizational development in village governance. The targets of this research are government administration system innovation, community service system innovation, tourism economic innovation, education innovation in the Wukirsari Village Government, Sleman Regency. In understanding the innovation process, researchers use the theory of innovation implementation. The emphasis of the theory is individual factors, structural factors and cultural factors. This means that the innovation strategy of the development of the Wukirsari Village Government organization can be seen from how the individuals in the village government and the village community run well, so that it can affect the existing structure and culture. The results of the research are the implementation of electronic organizational development innovations can improve the skills of the village government and the community of Wukirsari Village. Meanwhile, several innovations in the public service program, namely government administration system innovation in the form of Population Administration Data System (Sidampak), community service system innovation in the form of the Lukadesi system, My Birthday and Sidanik, economic innovation and tourism in the form of owl conservation programs, Tyto Alba, innovation education in the form of smart school programs. Keywords: Organizational Development, Innovation of government administration systems, Innovation of community service systems, Tourism economic innovation, Innovation in education